Neurological manifestations in COVID-19 infection - Wirawan, Chandra; ., Shierly (International Journal of Research in Medical Sciences, 2020)
The emerge of coronavirus disease 2019 (COVID-19), previously known as novel coronavirus (2019-nCoV), in Wuhan, China, in December 2019, has spread throughout the world. COVID-19 is known to cause respiratory disease. However, several scientific studies have shown nervous system involvement in COVID-19 infection. The potential mechanisms of this infectious disease transmission to the brain are through infected olfactory epithelium, hematogenous spread and immune-related pathway. Nervous system involvement in COVID-19 infection can be classified as central nervous system (CNS) involvement, peripheral nervous system involvement (PNS) and muscle. CNS involvement, including headache, cerebrovascular disease, impaired consciousness, meningitis, encephalitis, dizziness and seizure. PNS manifestations, such as anosmia, ageusia or dysgeusia, oculomotor nerve palsy and Guillain-Barre syndrome (GBS). Myalgia or arthralgia is the most common presentation of muscle involvement in COVID-19 infection. This review concludes that neurological disorders as COVID-19 clinical features must be recognized by medical professionals in order to have appropriate diagnosis and treatment so that COVID-19 patients can have better prognosis.